2007
DOI: 10.1016/j.geoderma.2007.03.011
|View full text |Cite
|
Sign up to set email alerts
|

A single layer soil water balance model for estimating deep drainage (potential recharge): An application to cropped land in semi-arid North-east Nigeria

Abstract: The understanding and quantification of groundwater recharge in semi-arid areas are fundamental to sound management of water resources in such areas. A soil water balance model, if designed to adequately represent the physical processes involved, and if carried out with a short enough (daily) time step, can provide realistic estimates of deep drainage (potential recharge) over long periods.We describe a single store (single layer) mass water balance model applicable to semi-arid areas, which recognises the wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 15 publications
3
42
0
2
Order By: Relevance
“…Annual drainage rates below 120 cm soil depth ranged from 477.8 to 1565.9 mm and depended on the intensity and frequency of rainfall events and especially soil water storage from the preceding dry periods. A similar trend in drainage was also reported by Eilers et al (2007), Aydin (2008). The long-term mean annual drainage-loss was approximately two times higher than actual soil evaporation.…”
Section: Resultssupporting
confidence: 85%
“…Annual drainage rates below 120 cm soil depth ranged from 477.8 to 1565.9 mm and depended on the intensity and frequency of rainfall events and especially soil water storage from the preceding dry periods. A similar trend in drainage was also reported by Eilers et al (2007), Aydin (2008). The long-term mean annual drainage-loss was approximately two times higher than actual soil evaporation.…”
Section: Resultssupporting
confidence: 85%
“…Contributing to the non-linearity of the relationship between rainfall and recharge, some studies suggest that a certain threshold of rainfall (annual or event-driven) must be reached before any recharge to groundwater occurs. The large inter-annual variability of rainfall, thus, may lead to large inter-annual variability of recharge (Eilers et al, 2007;Edmunds, 2009;Olago et al, 2009). Insignificant recharge is thought to occur when rainfall is generally less than 200 mm yr -1 , though some recharge during individual intense events less than that amount (Scanlon, et al, 2006;Edmunds 2009).…”
Section: Alterations To Surface Water and Groundwatermentioning
confidence: 99%
“…One study observed recharge taking place approximately every 10 years for a duration of a 3-year pluvial event (Olago et al, 2009). Individual intense events, in general, may be contributing more to recharge than the sum of all daily rainfall events (Taylor and Howard, 1996;Eilers et al, 2007;Owor et al, 2009). The decline of groundwater levels has been observed during periods of sustained annual reduction of rainfall such as during drought.…”
Section: Alterations To Surface Water and Groundwatermentioning
confidence: 99%
“…Butterworth et al, 1999). While recharge proportions in excess of 10% are possible in some areas with mean annual rainfall below 500 mm, the proportion is generally less than this, typically falling to negligible for areas with rainfall below 200 mm/year (Lerner et al, 1990;Scanlon et al, 2006;Eilers et al, 2007;Edmunds, 2008;WHYMAP, 2008). Figure 4 shows a simplified groundwater resources map for Africa.…”
Section: Groundwater Resources In Africamentioning
confidence: 99%
“…In addition, the permeability and porosity of underlying aquifers can limit the capacity for recharge to be stored. Nonetheless, for the purpose of making a general assessment for the whole of Africa, it is reasonable to assume that negligible recharge occurs in areas with annual rainfall of less than 200 mm (Eilers et al, 2007), and that recharge of up to approximately 50 mm can occur in areas with annual rainfall in the range of 200-500 mm (De Vries & Simmers, 2002;Edmunds, 2008), and greater in areas where rainfall exceeds 500 mm (e.g. Rueedi et al, 2005).…”
Section: Estimating the Impact Of Changing Groundwater Recharge Patternsmentioning
confidence: 99%